2003
DOI: 10.1176/appi.ps.54.3.356
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Psychiatric Hospital Readmission Among Children and Adolescents in State Custody

Abstract: The findings of this study highlight the significance of enabling factors, notably living arrangement, geographic region, and posthospital services, for children and adolescents in the child welfare system. Prevention of readmission among these children must focus on community-based services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
118
2
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(129 citation statements)
references
References 61 publications
8
118
2
1
Order By: Relevance
“…Children with ASD or other developmental disabilities may be at greater risk for psychiatric hospitalization than children with other disorders (Gallaher et al 2002;Romansky et al 2003;Saeed et al 2003;Walsh et al 1997). Studies have found that a quarter of children with ASD served in community mental health settings have been psychiatrically hospitalized and that children with ASD have five times the Medicaid-reimbursed expenditures for inpatient psychiatric care of children with mental retardation and 20 times that of children with other psychiatric diagnoses (Croen et al 2006;Mandell et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Children with ASD or other developmental disabilities may be at greater risk for psychiatric hospitalization than children with other disorders (Gallaher et al 2002;Romansky et al 2003;Saeed et al 2003;Walsh et al 1997). Studies have found that a quarter of children with ASD served in community mental health settings have been psychiatrically hospitalized and that children with ASD have five times the Medicaid-reimbursed expenditures for inpatient psychiatric care of children with mental retardation and 20 times that of children with other psychiatric diagnoses (Croen et al 2006;Mandell et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…As hospitals continue to adapt to a changing health care environment where resources are limited and pressures to reduce lengths of stay are great, more information is needed about effective strategies to reduce readmissions. Understanding factors that contribute to readmission is essential not only for continued quality improvement, but also for the development of targeted prevention programs aimed at those at greatest risk.The few existing studies (Arnold et al, 2003;Blader, 2004;Romansky, Lyons, Lehner, & West, 2003) that have examined predictors of readmission among children and adolescents vary considerably with regard to design (retrospective versus prospective), data source (hospital records versus administrative data), operational definition of readmission (to the same hospital versus any hospital in the state or managed care network), population (publicly insured versus privately insured), and type of predictor variables examined. Consequently, methodological differences across studies make it difficult to integrate findings or draw definitive conclusions about factors that lead to readmissions.…”
mentioning
confidence: 99%
“…Some investigators (e.g., Arnold et al, 2003;Foster, 1999;Pavkov, Goerge, & Lee, 1997) have found an association between child's age and readmission, while others (e.g., Blader, 2004; Cornsweet-Barber & Evans, 1999;Romansky et al, 2003) have not. Neither race nor gender has been found to consistently predict readmission (Arnold et al, 2003;Blader, 2004;Foster, 1999;Pavkov et al, 1997;Romansky et al, 2003).The strong association between various clinical factors and readmission, particularly diagnosis and severity of symptoms, is well documented in the research literature; youths diagnosed with affective, behavioral disorders and/or psychoses with more severe symptoms are at greater risk for readmission (Arnold et al, 2003;Blader, 2004;Foster, 1999;Pavkov et al, 1997). The influence of other clinical factors such as suicidal and homicidal behavior, history of abuse, and comorbidity is less clear and has not been consistently examined by researchers.…”
mentioning
confidence: 99%
“…Two prior studies of rehospitalization risk included a significant number of preadolescents in cohorts that combined children and adolescents (mean age 13 years), but the samples comprised dependents of military personnel (Foster, 1999) and children in state custody (Romansky et al, 2003). Another study followed a predominantly adolescent sample discharged from longterm state hospitals (mean age 14.5 years) (Pavkov et al, 1997); this group may not generalize to the majority of hospitalized children, who are admitted to acute-care units (Pottick et al, 2000).…”
mentioning
confidence: 99%